Role of leadership and participation: Social innovation in health in selected provinces in the Philippines. Issue 4 (31st October 2019) - Gallardo, Rita M.
Abstract : Purpose: The purpose of this paper is to offer pointers to local government executives on the qualities of leadership that drive social innovation (SI) as well as locate the roles of leadership and participation in the output and outcome of SI. Further, the findings of the study can hopefully contribute to the discourse on leadership for a sustainable future. Design/methodology/approach: The purpose of the study was to highlight the forms of participation among the actors in the different stages of SI, the qualities of the leaders that drove SI and the roles of leadership and participation in the output and outcome of SI. To answer the research questions, the researcher applied the case study research design and employed the grounded theory approach for data analysis and interpretation. Findings: The cases showed leadership that encourages, as leadership qualities of the governors. These were manifested in terms of being empowering, giving the freehand, being goal-oriented, resource mobilizer, consultative and practicing both bottom-up and top-bottom approaches to make sure that the outputs are achieved, as well as having the qualities of a supportive leader. The cases showed all three employed forms of participation, as categorized by Lowndes et al. (2001). Government can indeed foster innovation when there is close involvement and participation of the workforce in innovation. Leadership and participation play a big role in achieving output and outcome of SI. Originality/value: The study is a review of the unpublished dissertation by Gallardo (2014) at the National College of Public Administration and Governance, University of the Philippines.